Signet ring cell carcinoma of resectable metastatic colorectal cancer has rare surgical value. Issue 8 (27th November 2016) - Fu, Jianfei; Wu, Lunpo; Jiang, Mengjie; Tan, Yinuo; Li, Dan; Chen, Fei; Jiang, Ting; Du, Jinlin
Abstract : Background and Objectives: Signet ring cell carcinoma (SRCC) is a uniquely separated subgroup in metastatic colorectal cancer (mCRC). The aims are to investigate the value of resection in patients with resectable metastatic signet ring cell colorectal cancer. Methods: Patients with mCRC who underwent resection in Surveillance, Epidemiology, and End Results database during 1998–2010 were retrospectively analyzed. Kaplan–Meier and COX models were used to analyze the differences in the survival. Logistic regression models were used to evaluate the relationship between SRCC and other clinicopathological factors. Results: Among the 3, 568 patients, 94 (2.63%) patients had SRCC. The median survival time of patients with SRCC and non‐SRCC were 17 and 29 months, respectively ( P  < 0.001). Multivariate analysis indicated that SRCC was an independent prognostic factor for poor overall survival. Logistic regression model based on variables identified by univariate analysis indicated that younger age (≤50 years old) ( P  = 0.005), female ( P  < 0.001), location in colon ( P = 0.012), and N positive status ( P = 0.003) were independent variables correlated with the SRCC subgroup. SRCC had a dramatically higher invalid surgical outcome rate than non‐SRCC ( P = 0.001). Conclusion: SRCC patients might benefit little from the resection of primary and metastatic lesions with a high rate of undergoing invalid operations. J. Surg. Oncol. 2016;114:1004–1008 . © 2016 Wiley Periodicals, Inc.